2005
DOI: 10.4161/cc.4.4.1585
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptides, A Chemical Genetics Tool for Biologists

Abstract: The genomics era has presented scientists with an overwhelming amount of sequence information that encodes for a continuously expanding array of metabolic pathways and regulatory networks. In order to unravel this elaborate maze, effective approaches need to be pioneered, and cyclic peptides represent an exciting new tool that can aid this challenging task. There are considerable benefits to cyclic peptides including enhanced protein binding affinity and metabolic stability, but perhaps most important is the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Toward this end, a method to generate libraries of cyclic peptides that employs circularly permuted inteins which self-catalyze the cyclization of a target peptide has been developed in Escherichia coli (16)(17)(18)(19)(20)(21)(22). This method, termed split intein catalyzed ligation of proteins and peptides (SICLOPPS), has been previously used to select inhibitors of hydrolases, methyl transferases, and other proteins (17,20,(22)(23)(24).…”
mentioning
confidence: 99%
“…Toward this end, a method to generate libraries of cyclic peptides that employs circularly permuted inteins which self-catalyze the cyclization of a target peptide has been developed in Escherichia coli (16)(17)(18)(19)(20)(21)(22). This method, termed split intein catalyzed ligation of proteins and peptides (SICLOPPS), has been previously used to select inhibitors of hydrolases, methyl transferases, and other proteins (17,20,(22)(23)(24).…”
mentioning
confidence: 99%
“…After 5 min, 30 ȝg/ml ampicillin was added to the cultures and growth was monitored at 37°C. ȕ Cyclic peptide or protein libraries are extremely useful as they can be exploited for genetic study or peptide inhibitor screening (Horswill and Benkovic, 2005). Studies have shown that cyclic proteins, with their N-and C-termini linked by a normal peptide bond, are easily generated using split inteins.…”
Section: Namementioning
confidence: 99%
“…The orthogonal aaRS/tRNA(CUA) pairs were expressed in Escherichia coli ( E. coli) in order to assign L- p -benzoylphenylalanine to the amber codon [46]. Additionally, the split intein catalyzed ligation of proteins and peptides (SICROPPS) method, which was developed by Benkovic's group [70, 71], was used to cyclize the backbone of a ribosomally synthesized peptide library containing L- p -benzoylphenylalanine. The activity-based in-cell selection of human immunodeficiency virus (HIV) protease inhibitors from the cyclic peptide library was performed by linking the protease inhibitory activity of a cyclic peptide to cell viability of the host E. coli .…”
Section: Selection Of Functional Nonstandard Peptides Generated Bymentioning
confidence: 99%